Design of recustomize finite impulse response filter using truncation based scalable rounding approximate multiplier and error reduced carry prediction approximate adder for image processing application. (30th January 2023) - Senthilkumar, S.; Samuthira Pandi, V.; Sripriya, T.; Pragadish, N.
Summary: Recustomize finite impulse response (RFIR) filter is designed to achieve lesser power consume, cost, area, and higher speed of system operation. This is used to remove the noises from the image and signal. Previously, several filters were designed for removing noises, but that filters consume more area, power, cost, and delay and did not provide accurate results and the error rate was increased. To overcome these issues, this work is proposed. In this work, the Recustomize finite impulse response (RFIR) filter is designed using truncation‐based scalable rounding approximate multiplier (TOSAM) and error reduced carry prediction approximate adder (ERCPAA) for image processing application. Here, TOSAM‐ERCPAA is used to speed up the filter design with less area and less power consumption. The proposed ERCPAA adder is divided into three blocks, such as carry prediction logic, approximate full adder cells array, constant truncation along error lessening logic, which can reduce the power and area. The proposed RFIR‐ TOSAM‐ERCPAA filter is designed and executed in Verilog programming language and the simulation is done in Xilinx ISE 14.5 design tools.